2010
DOI: 10.1111/j.1600-0714.2010.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of bisphosphonate-induced jaws osteonecrosis in Sprague-Dawley rats

Abstract: The administration of pamidronate and dexamethasone in rats subjected to molar extraction increases the risk of osteonecrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…By extracting only the second maxillary molar we were able to produce BRONJ in the experimental group (See Fig. 3) (17,15,20-22), while previous studies had extracted all hemimandible molars to obtain the same result (20,22). …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By extracting only the second maxillary molar we were able to produce BRONJ in the experimental group (See Fig. 3) (17,15,20-22), while previous studies had extracted all hemimandible molars to obtain the same result (20,22). …”
Section: Discussionmentioning
confidence: 83%
“…We also observed that the experimental group exhibit evident delayed reepithelialization at the fourth week, in contrast with other BRONJ models which showed the same condition but during a longer period of time. (2,9,22,23)…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of BRONJ in patients receiving long-term oral BP therapy was reported to be approximately 0.1% [11]. Recently, BRONJ-like models have been established in various animals [25,26,[42][43][44]. The administration of BPs combined with dexamethasone induced BRONJ-like models with exposed bone in some studies [25,43,44], is clinically relevant because most cancer patients receive multiple immunosuppressive drugs, including dexamethasone and chemotherapeutic agents [45].…”
Section: Discussionmentioning
confidence: 96%
“…This variability has been hypothesized to be due to the type, route of administration, and dose regimen of BP delivery, in combination with the lack of well-defined outcome measures that define the presence of ONJ in rodents [30]. It is noteworthy, that studies consistently reporting ONJ-like features in mice or rat extraction models include in their experimental design systemic risk factors such as steroid or chemotherapy treatment, vitamin D deficiency, or diabetes all of which alter soft tissue and/or bone homeostasis and compound wound healing [68, 10, 12, 3739]. …”
Section: Discussionmentioning
confidence: 99%